How to Get a Job in Television - Sharp, Elsa (Professional Media Practice, 2014)
'Incredibly timely, practical advice for developing contacts and skills' Jo Taylor, 4Talent Manager at Channel 4TV is a notoriously difficult industry to get into and progress within. There is no set career path and 70% of applicants rely on contacts to get a foothold. Based on the author's experience as a TV researcher, series producer and recruitment executive, this contemporary guide will help thousands of hopefuls break into TV. It is packed with inside information and advice from training bodies, HR executives, and people working in the industry at every level, including for example: Conrad Green - the multi award-winning British Executive Producer of American Idol and Dancing With the Stars (US) Tim Hincks - Chairman of Endemol (makers of Big Brother) Grant Mansfield - Chairman and MD of RDF Television Kate Phillips - Head of Development at BBC TVFrom the do's and don'ts of work experience, the role of the researcher, the 'seven stages of CV', pathways to series producer and how to move up the ladder, this is the TV job hunter's bible.